Case of Glantz v. Finland (Application No. 37394/11) - Karaçoban Güneş, Tuğçe (Seçkin Yayıncılık, 2017)
Mr Glantz Finnish citizen assertedthat the Article 4 of the Supplementary protocol No 7 of the European Convention on Human Rights was breach conceming the assertion that due to the additional tax assessment and administrative fine implemented against him, the criminal suit that was filed against him has the characteristics of double jeopardy for the same criminal action. The European Court of Human Rights (ECHR) evalualed the case in terms of The Four elemennts of nonbis in idem principle which are as follows “whether it ıs a criminal adjucation” “whether the crimes for which the applicant is charged are the same” “whether ares judicata is presented” and “whether there were duplicate proceedings”

Fin vatandaşı olan Kaj Erik Torsten Glantz aleyhinde yapılan ek tahakkuk ve idari para cezası ile nitelikli vergi kaçaklığı suçu nedeniyle yürütülen ceza davasının aynı suç nedeniyle iki kez yargılanma niteliği taşıdğından bahisle Avrupa İnsan Hakları Sözleşmesi’nin 7 no.lu Ek Protoklü’nün 4. Maddesinin ihlal edildiğini ileri sürmüştür. Avrupa İnsan Hakları Mahkemesi non bis in idem ilkesinin “ceza muhakemesi” “başvuranın yargılandığı suçların aynı olup olmadığı” “kesin bir hükmün mevcut olup olmadığı” ve iki kez yargılama ve cezalandırmanın söz konusu olup olmadığı” olarak adlandırılan dört unsuru bakımından detaylı bir değerlendirme yapmıştır.
Keywords: Principle of Non Bis In Idem; Tax Sanction Law; Glantz v. Finland Decision; Engel’s Criteria; Taxational Misdemeanors; Non Bis Idem İlkesi; Vergi yaptırım hukuku; Glantz v. Finlandiya Kararı Engel Kriterleri; Vergi Kabahatleri